1) ОДЗ :
x² - 2x - 2 > 0
0" alt="D=(-2)^{2}-4*(-2)=4+8=12=(2\sqrt{3} )^{2}\\\\x_{1}=\frac{2+2\sqrt{3} }{2}=1+\sqrt{3}\\\\x_{2}=\frac{2-2\sqrt{3} }{2}=1-\sqrt{3}\\\\(x -(1+\sqrt{3}))(x-(1-\sqrt{3}))>0" align="absmiddle" class="latex-formula">
+ - +
__________₀___________₀___________
1 - √3 1 + √3
x ∈ (- ∞ ; 1 - √3) ∪ (1 + √3 ; + ∞)
![lg(x^{2}-2x-2)\leq0\\\\x^{2}-2x-2\leq 1\\\\x^{2}-2x-3\leq0\\\\(x-3)(x+1)\leq0 lg(x^{2}-2x-2)\leq0\\\\x^{2}-2x-2\leq 1\\\\x^{2}-2x-3\leq0\\\\(x-3)(x+1)\leq0](https://tex.z-dn.net/?f=lg%28x%5E%7B2%7D-2x-2%29%5Cleq0%5C%5C%5C%5Cx%5E%7B2%7D-2x-2%5Cleq%201%5C%5C%5C%5Cx%5E%7B2%7D-2x-3%5Cleq0%5C%5C%5C%5C%28x-3%29%28x%2B1%29%5Cleq0)
+ - +
__________[- 1]___________[3]_________
///////////////////////////
x ∈ [ - 1 ; 3]
С уч1том ОДЗ окончательный ответ :
x ∈ [- 1 ; 1 - √3) ∪ (1 + √3 ; 3]
2)
1) x > 0
0\\\\x > 1\\\\3)log_{\frac{1}{3} }(log_{5}x)>0\\\\log_{5}x<1\\\\x< 5" alt="2) log_{5}x>0\\\\x > 1\\\\3)log_{\frac{1}{3} }(log_{5}x)>0\\\\log_{5}x<1\\\\x< 5" align="absmiddle" class="latex-formula">
Окончательно : x ∈ (1 ; 5)
0\\\\log_{\frac{1}{3} }(log_{5}x)>1\\\\log_{5}x<\frac{1}{3}\\\\x<5^{\frac{1}{3} }\\\\x<\sqrt[3]{5}" alt="log_{2} (log_{\frac{1}{3} }(log_{5}x))>0\\\\log_{\frac{1}{3} }(log_{5}x)>1\\\\log_{5}x<\frac{1}{3}\\\\x<5^{\frac{1}{3} }\\\\x<\sqrt[3]{5}" align="absmiddle" class="latex-formula">
Ответ : ![x\in(1;\sqrt[3]{5} ) x\in(1;\sqrt[3]{5} )](https://tex.z-dn.net/?f=x%5Cin%281%3B%5Csqrt%5B3%5D%7B5%7D%20%29)